Activation and function of mitochondrial uncoupling protein in plants. - Smith, A; Ratcliffe, R; Sweetlove, L (2004)
Plant mitochondrial uncoupling protein (UCP) is activated by superoxide suggesting that it may function to minimize mitochondrial reactive oxygen species (ROS) formation. However, the precise mechanism of superoxide activation and the exact function of UCP in plants are not known. We demonstrate that 4-hydroxy-2-nonenal (HNE), a product of lipid peroxidation, and a structurally related compound, trans-retinal, stimulate a proton conductance in potato mitochondria that is inhibitable by GTP (a characteristic of UCP). Proof that the effects of HNE and trans-retinal are mediated by UCP is provided by examination of proton conductance in transgenic plants overexpressing UCP. These experiments demonstrate that the mechanism of activation of UCP is conserved between animals and plants and imply a conservation of function. Mitochondria from transgenic plants overexpressing UCP were further studied to provide insight into function. Experimental conditions were designed to mimic a bioenergetic state that might be found in vivo (mitochondria were supplied with pyruvate as well as tricarboxylic cycle acids at in vivo cytosolic concentrations and an exogenous ATP sink was established). Under such conditions, an increase in UCP protein content resulted in a modest but significant decrease in the rate of superoxide production. In addition, 13C-labeling experiments revealed an increase in the conversion of pyruvate to citrate as a result of increased UCP protein content. These results demonstrate that under simulated in vivo conditions, UCP is active and suggest that UCP may influence not only mitochondrial ROS production but also tricarboxylic acid cycle flux.